Biomonitoring of atmospheric pollution by moss bags: Discriminating urban-rural structure in a fragmented landscape. (April 2016) - Capozzi, F.; Giordano, S.; Di Palma, A.; Spagnuolo, V.; De Nicola, F.; Adamo, P.
Abstract: In this paper we investigated the possibility to use moss bags to detect pollution inputs - metals, metalloids and polycyclic aromatic hydrocarbons (PAHs) - in sites chosen for their different land use (agricultural, urban/residential scenarios) and proximity to roads (sub-scenarios), in a fragmented conurbation of Campania (southern Italy). We focused on thirty-nine elements including rare earths. For most of them, moss uptake was higher in agricultural than in urban scenarios and in front road sites. Twenty PAHs were analyzed in a subset of agricultural sites; 4- and 5-ringed PAHs were the most abundant, particularly chrysene, fluoranthene and pyrene. Overall results indicated that investigated pollutants have a similar spatial distribution pattern over the entire study area, with road traffic and agricultural practices as the major diffuse pollution sources. Moss bags proved a very sensitive tool, able to discriminate between different land use scenarios and proximity to roads in a mixed rural-urban landscape. Graphical abstract: Highlights: Moss bag sensitivity was tested in an urban-rural fragmented landscape. Moss uptakes were overall higher in agricultural than in urban sites. Mosses were able to discriminate between front road and matching green sites. Traffic and intensive agriculture are the major pollution sources in the study area.